A novel method for the measurement of glucocorticoids in dermal secretions of amphibians. Issue 1 (16th February 2018) - Santymire, R M; Manjerovic, M B; Sacerdote-Velat, A
Abstract : We are developing a novel method using non-invasive skin swabs to measure stress in several amphibians from terrestrial, semi-aquatic and fully aquatic species both at the zoo and in the wild. Upon further testing, this technique will allow future studies to understand how the environment is impacting amphibian health and susceptibility to disease. Abstract: Amphibians have been declining in both diversity and abundance due in large part to habitat degradation and the prevalence of emerging diseases. Although stressors can suppress the immune system, affecting an individual's health and susceptibility to pathogens, established methods for directly collecting stress hormones are not suitable for rapid field use or for use on threatened and endangered species. To overcome these challenges, we are developing an innovative method to collect and measure amphibian glucocorticoid secretions using non-invasive dermal swabs. We tested this methodology using multiple terrestrial, semi-aquatic and fully aquatic species. We swabbed the dorsal side of each animal six times and then induced a stressor of either hand-restraint, ACTH injection, or saline as a control. We then repeated swab collection immediately after the stressor and at 15, 30, 45, 60, 90 and 120 min intervals. Cortisol enzyme immunoassay detected changes in cortisol post-stressor. We also tested this methodology in the field and were successfully able to detect glucocorticoids from multiple species at varying life stages. When using in the field, capture technique should be considered since it may impact stress levels in certain species. Upon further testing, this novel method may be used to greatly increase our understanding of amphibian health especially as disease and environmental changes continue to impact fragile populations.